METODE IMAM ASY-SYAUKANI DALAM MENYUSUN KITAB NAILUL AUTAR SYARH MUNTAQAL-AKHBAR - Fauzi Rizal (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
This article aims to describe the method of Imam Asy-Syaukani in compiling the book Nailul Autar Syarh Muntaqal-Akhbar. Kitab Nailul Authar is a book of shar from the book of legal hadith compiled by ibn Taimiyan "al-Muntaqa" consisting of 5029 traditions, then disyarh by Asy-Syaukani to 8 juz, each of 380 pages, up to 3040 pages. Therefore, the author tries to give a picture of the intended book.